2019
DOI: 10.1021/acs.inorgchem.9b01678
|View full text |Cite
|
Sign up to set email alerts
|

Neutral Cyclometalated Iridium(III) Complexes Bearing Substituted N-Heterocyclic Carbene (NHC) Ligands for High-Performance Yellow OLED Application

Abstract: The synthesis, crystal structure, and photophysics of a series of neutral cyclometalated iridium(III) complexes bearing substituted N-heterocyclic carbene (NHC) ancillary ligands ((C ∧ N) 2 Ir(R-NHC), where C ∧ N and NHC refer to the cyclometalating ligand benzo[h]quinoline and 1-phenylbenzimidazole, respectively) are reported. The NHC ligands were substituted with electron-withdrawing or -donating groups on C4′ of the phenyl ring (R = NO 2 (Ir1), CN (Ir2), H (Ir3), OCH 3 (Ir4), N(CH 3 ) 2 (Ir5)) or C5 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 57 publications
(88 reference statements)
1
21
0
Order By: Relevance
“…In water, the vibronic structures of this absorption band were less pronounced and the band became broader due to the aggregation of BODIPY‐Ir. The Ir(NHC)(bqu) 2 (bqu represents benzo[ h ]quinoline) motif mainly contributes to the absorption in the regions of <500 nm referring to the absorption spectrum of Ir(NHC)(bqu) 2 reported in our previous studies [ 19k,22 ] and confirmed by the TDDFT calculation results shown in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 75%
“…In water, the vibronic structures of this absorption band were less pronounced and the band became broader due to the aggregation of BODIPY‐Ir. The Ir(NHC)(bqu) 2 (bqu represents benzo[ h ]quinoline) motif mainly contributes to the absorption in the regions of <500 nm referring to the absorption spectrum of Ir(NHC)(bqu) 2 reported in our previous studies [ 19k,22 ] and confirmed by the TDDFT calculation results shown in Table S1, Supporting Information.…”
Section: Resultssupporting
confidence: 75%
“…Since then numerous heteroleptic Ir(III)-7,8-benzoquinoline complexes were reported with very same coordination mode. [12][13][14][15][16][17][18] The Ir-benzoquinoline complexation could be viewed as the formation of initial Ir-N(quinoline) bond, which selectively induces the C10-H bond activation and leads to Ir-C10 coordination. This results in a stable vemembered chelation by 7,8-benzoquinoline.…”
mentioning
confidence: 99%
“…The Ir-C, Ir-N and Ir-Cl [2.3683( 12) A] bond lengths in complex (2) were in good agreement with the values reported for several similar Ir(III) complexes. 13,32 The structure of complex (3) displayed two benzoquinoline ligands in different coordination modes. One of them had the ortho C-H bond activation and coordinated in a monodentate way through C14 to the iridium centre, whereas the other benzoquinoline had acted as a bidentate ligand and chelated the Ir(III) centre through N1 and C11.…”
mentioning
confidence: 99%
See 2 more Smart Citations